Immunometabolic T cell failure induces multimorbidity and aging - Desdín Micó, Gabriela; Soto Heredero, Gonzalo; Aranda, Juan Francisco; Oller, Jorge; Carrasco, Elisa; Gabandé Rodríguez, Enrique; Blanco, Eva María; Alfranca, Arantzazu; Cusso, Lorena; Desco, Manuel; Ibañez, Borja; Gortazar, Arancha R.; et al. (My University, 2020)
The impact of immunometabolism on age-associated diseases remains uncertain. Here, we show that T cells with dysfunctional mitochondria act as aging accelerators. They instigate multiple age-related features, including metabolic, cognitive, physical and cardiovascular alterations, which together result in premature death. Metabolic failure in T cells induces the accumulation of circulating cytokines, resembling the chronic inflammation that characterizes aging (¿inflammaging¿). We also present evidence that this cytokine storm is a systemic inducer of senescence. Dampening inflammation by blocking TNF-¿ signaling or preventing senescence with NAD+ precursors partially rescue premature aging in mice with metabolically defective T cells. Thus, T cells have the capacity to regulate organismal fitness and lifespan, highlighting the importance of tight immunometabolic control in both aging and the onset of age-associated diseases